Doxifluridine effectively kills antibiotic-resistant Staphylococcus aureus in chronic obstructive pulmonary disease - Lianshen Zhang; Yingzhang Zhang; Lijie Tian; Qiang Shen; Xiaolong Ma (Microbiology Spectrum)
ABSTRACT Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality globally, often exacerbated by infections such as methicillin-resistant Staphylococcus aureus (MRSA). The rise in antibiotic-resistant strains complicates treatment and underscores the need for novel therapeutic drugs. In this paper, we further investigated the antimicrobial potential of a fluoropyrimidine anticancer drug doxifluridine against multidrug-resistant S. aureus. Determination of minimum inhibitory concentration (MIC) or minimum bactericidal concentration (MBC), monitoring of growth curve, time-kill assays, biofilm bactericidal assays, and chequerboard studies were conducted to evaluate the antibacterial efficacy of doxifluridine. Safety was assessed via hemolysis and cytotoxicity assays, and an in vivo Galleria mellonella larvae model was employed to test protective effects. Doxifluridine demonstrated significant antibacterial activity against clinical multidrug resistance (MDR) S. aureus isolates, with MIC and MBC values ranging from 0.5 to 2 µg/mL and 1 to 4 µg/mL, respectively. The results revealed doxifluridine’s potent bactericidal effects within 8 hours. Moreover, doxifluridine-treated bacteria showed a substantial reduction in biofilm mass and viability. Furthermore, chequerboard assays indicated synergistic interactions between doxifluridine and other antibiotics, reducing MIC values by two- to eightfold. More importantly, safety evaluations confirmed that doxifluridine did not exhibit hemolytic toxicity or cytotoxicity. Finally, doxifluridine significantly increased the survival rate of MRSA-infected G. mellonella larvae in vivo. In brief, doxifluridine exhibited promising in vitro and in vivo antibacterial activity against MRSA, suggesting its potential as a repurposed drug for treating resistant bacterial infections in COPD patients.IMPORTANCEThe study provides robust evidence for the antibacterial efficacy of doxifluridine against Methicillin-resistant Staphylococcus aureus in chronic obstructive pulmonary disease (COPD) patients. Its rapid action, ability to disrupt biofilms, and synergistic effects with other antibiotics, combined with a favorable safety profile, highlight its potential as a repurposed therapeutic agent. Future clinical trials will be essential to confirm these findings and pave the way for its integration into clinical practice. This work not only provides candidate for tackling the management of bacterial infections in COPD but also exemplifies the potential of drug repurposing in combating antibiotic-resistant infections.